SYNTHESIS AND CHARACTERIZATION OF SUBSTITUTED 1,2,3-TRIAZOLES COMBINED WITH $γ$-BUTANOLIDE RING (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
The synthesis of new 1,2,3-triazoles has been actualized by means of the reaction of dipolar1,3-cycloaddition of organic azides to the $γ$-lactones containing terminal triple bond. The synthesized compounds previously were nondescript in literature. High yields of the final products ensured the optimal reaction conditions.
Keywords: 1,2,3-triazoles, butanolides, 1,3-cycloaddition, click-reaction